2004
DOI: 10.1039/b407302a
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure of nitrilimines revisitedElectronic supplementary information (ESI) available: Optimized structures and absolute energies of all stationary points. See http://www.rsc.org/suppdata/cc/b4/b407302a/

Abstract: A combination of density-functional theory and natural resonance theory has been used to show that a complete description of the electronic structure of nitrilimines, R(1)CNNR(2), requires four resonance structures (propargylic, allenic, 1,3-dipolar and carbenic); appropriate substituents were shown to enhance the carbene character of nitrilimines to the point where they may be considered stable carbenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 17 publications
5
29
0
Order By: Relevance
“…[69] Weinholds natural resonance theory (NRT) has also been applied by Mawhinney et al towards understanding the electronic structure of nitrilimines. [70] They concluded that nitrilimines had significant carbene character. However, Ponti and co-workers have used CASSCF and spin-coupled calculations to show that the most important electronic structure of nitrilimines corresponds to the propargylic resonance form with little or no carbenic character.…”
Section: Configuration Mixing Modelsmentioning
confidence: 99%
“…[69] Weinholds natural resonance theory (NRT) has also been applied by Mawhinney et al towards understanding the electronic structure of nitrilimines. [70] They concluded that nitrilimines had significant carbene character. However, Ponti and co-workers have used CASSCF and spin-coupled calculations to show that the most important electronic structure of nitrilimines corresponds to the propargylic resonance form with little or no carbenic character.…”
Section: Configuration Mixing Modelsmentioning
confidence: 99%
“…These equations can readily be expanded to include additional orbital interactions. Since the ethene orbitals are the same throughout and the shapes of the nitrilimine orbitals are qualitatively similar (32), one may assume that the atomic orbital coefficients are relatively constant, and their products may be approximated by a general factor (K). Additionally, the distance between the interacting centres is moderately invariant (Table 1), and so β may also be considered constant.…”
Section: Frontier Molecular Orbitalsmentioning
confidence: 99%
“…[20] Different ways to describe the geometric and electronic structures of the parent nitrile imine have also been reported by means of valence bond (VB) calculations. [20] Different ways to describe the geometric and electronic structures of the parent nitrile imine have also been reported by means of valence bond (VB) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly noticeable by the CNN antisymmetric stretching IR absorption of the nitrile imine moiety appearing over a wide range of frequencies (2000-2250 cm -1 ). [20,29,30] For instance, Bégué and Wentrup have theo-retically investigated different amino-, hydroxy-, and fluorosubstituted nitrile imines (R-CNN-H, H-CNN-R, and R-CNN-R; R = NH 2 , OH, and F) and predicted that some of the studied molecules should exhibit carbenic character. [17] In addition, theoretical studies have indicated that substituents bearing a lone-electron pair should increase the importance of the carbenic resonance structure of nitrile imines.…”
Section: Introductionmentioning
confidence: 99%